Efficacy of the membranous form of platelet-rich fibrin in root coverage - Sarduy Bermúdez, Lázaro (2024)
Objective: To evaluate the efficacy of the membranous form of platelet-rich fibrin associated with the coronally advanced flap in patients attended by consultation in periodontics at the Faculty of Stomatology of Villa Clara. Materials and methods: A longitudinal study was conducted at the Faculty of Stomatology, Villa Clara, Santa Clara, Cuba, from January 2016 to March 2017. The sample comprised 17 individuals selected using a purposive, non-probabilistic sampling method. The traditional coronally advanced flap procedure was applied to teeth with periodontal recession in this cohort. Additionally, a platelet-rich fibrin membrane, derived from autologous blood and prepared in the Regenerative Medicine Service of the same institution, was placed beneath the flap. The study analyzed the following variables: age, sex, recession length, Miller classification, root coverage, width and gain of inserted gingiva, evaluation categories, and therapeutic efficacy. Results: Root coverage percentage was higher in class I and increased over time in all Miller classes. Inserted gingival width and gain increased from one month to one year. The percentage efficacy was 93.18 %. Conclusions: Periodontal recession therapy, with the membranous form of platelet-rich fibrin associated with the coronally advanced flap, was considered effective in patients attended by consultation in periodontics at the Faculty of Stomatology of Villa Clara.